Relationship Between Gender and Community Resilience - ., Yuniarti; Januarita, R; Irasanti, S N; Respati, T (KnE Social Sciences, 2023)
Gender dynamics play a significant role in how individuals of both sexes are impacted by disasters and their ability to cope and recover from them. Resilience is viewed as both an inherent personal characteristic and a quality that can be developed through interactions with environmental factors. The purpose of this study is to investigate the relationship between gender and community resilience in Indonesia and Malaysia, conducted from March 2022 to April 2022. The research design utilized a quantitative-based cross-sectional approach, and convenience sampling was employed with a total of 707 respondents. An online questionnaire, available in Bahasa Indonesia, Malay, and English, was used to collect data. The questionnaire consisted of five domains: (1) Connection and Caring; (2) Resources; (3) Transformative Potential; (4) Disaster Management; and (5) Information and Communication. On average, respondents required approximately 15-20 minutes to complete the questionnaire. The results indicate a relationship between gender and resilience specifically within the domain of Disaster Management (domain 4). However, no significant relationship was found between gender and overall community resilience or resilience in the other domains. In conclusion, both genders have an equal opportunity to enhance resilience by developing aspects such as self-efficacy, persistence, low anxiety, control, and planning. Keywords: gender, community resilience, disaster